India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper explores key issues affecting the Indian economy and implications for fiscal, monetary, financial sector, and other structural policies. This paper evaluates the build-up of corporate and banking sector vulnerabilities in India, linked to the past macroeconomic slowdown and supply-side bottlenecks, particularly in the infrastructure sector; the nature, scope, and the effectiveness of macroprudential policies in India; the potential costs and benefits of gold monetization schemes in India; two recent episodes of financial market volatility-the taper tantrum of the summer of 2013 and the China spillover episode of the summer of 2015; effectiveness of India's capital controls using an arbitrage based approach; the relationship between Indian; and international market prices of cereals.